2011
DOI: 10.1093/eurpub/ckr144
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-pack nutrition labelling: are multiple formats a problem for consumers?

Abstract: Background: Nutrition labels are a potentially valuable tool to assist consumers in making healthy food choices. Front-of-pack labels are a relatively new format and are now widely used across many European countries, but it is unclear which of the many formats in use are best understood by consumers. It is also unclear whether the existence of multiple formats impedes understanding and use. This article addresses this question with findings from a study commissioned by the UK Food Standards Agency to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 9 publications
2
77
0
5
Order By: Relevance
“…industria guíen al consumidor hacia la selección de alimentos saludables (2)(3)(4) . En este contexto, el presente estudio demuestra que el efecto potencial del semáforo nutricional en el Ecuador varía según dimensiones de la población, especialmente edad, sexo, y el tamaño del lugar de residencia, reflejando el hecho de que el semáforo nutricional es conocido, observado y tomado en cuenta en el momento de compra y consumo de alimentos procesados.…”
Section: Referencias Bibliográficasunclassified
See 1 more Smart Citation
“…industria guíen al consumidor hacia la selección de alimentos saludables (2)(3)(4) . En este contexto, el presente estudio demuestra que el efecto potencial del semáforo nutricional en el Ecuador varía según dimensiones de la población, especialmente edad, sexo, y el tamaño del lugar de residencia, reflejando el hecho de que el semáforo nutricional es conocido, observado y tomado en cuenta en el momento de compra y consumo de alimentos procesados.…”
Section: Referencias Bibliográficasunclassified
“…El problema afecta a todas las personas, independiente de su edad, etnia, lugar de residencia o nivel socioeconómico (1) . Experiencias en varios países demuestran que un etiquetado nutricional puede contribuir a mejores decisiones en la compra de alimentos y a prevenir el sobrepeso y la obesidad (2)(3)(4) . Un sistema de etiquetado frontal con graficas a colores permite que los consumidores identifiquen alimentos saludables y, si se parece un semáforo, facilita aún más la selección de esta clase de alimentos (5)(6)(7)(8)(9) .…”
Section: Introductionunclassified
“…In 2013 it was reported that 60 % of foods found in supermarkets featured traffic light labels and five supermarkets had agreed to consistent labelling including Sainsbury's, Tesco, Co-op, Waitrose and Morrisons (6) . In 2013 the UK Government published a press release announcing new consistency guidelines (6) based partly on findings by Draper et al (7) that concluded 'multiple front-of-pack label formats in the marketplace may impede consumer comprehension and discourage use'. This finding supported previous research reports that found different presentation of nutrition information confusing (8,9) .…”
mentioning
confidence: 99%
“…Along with corn flakes and yoghurt, these four food types were chosen because they are commonly purchased products [62], vary widely in healthiness [46], often contain health claims [63] and consumers often make use of the nutrition information contained on the packs of these products [64]. These foods have also been studied frequently in the past, allowing the findings of this study to be compared with those of previous studies [55,[65][66][67][68][69][70][71][72][73][74][75].…”
Section: Food Typementioning
confidence: 99%